Design of Kinetic Typography Interaction based on the Structural Characteristics of Hangul - Lim, Sooyeon (International JOURNAL OF CONTENTS, 2016)
Kinetic typography is technology such as color, scale, position of the letter changes dynamically with time and it communicates information with aesthetics and originality. The purpose of this study is to identify the design factors in the formativeness of Hangul and present and implement the interaction design method of unique Hangul kinetic typography based on the scientific structure of Hangul. We implemented the Hangul kinetic typography system, which varies in sizes and motion directions according to a viewer’s movement and exhibited in a media art event. To do this, we used a viewer’s skeleton information on typography synchronization. The results indicated that Hangul kinetic typography has potential not only as a means to communicate with viewers but also as a medium to show the artistic value of Hangul. KCI Citation Count: 1